Still city : poems - Maksymchuk, Oksana (University of Pittsburgh Press, 2024)
First-Hand and Documentary Poetic Witness to the War in Ukraine.
Description based upon print version of record.
Keywords: Russo-Ukrainian War, 2014- -- Poetry.; War and society -- Poetry.; War -- Psychological aspects -- Poetry.; Ukraine -- Poetry.; Ukrainian American poetry -- 21st century.; Guerre et société -- Poésie.; Guerre -- Aspect psychologique -- Poésie.; Russian & Former Soviet Union.; Death.; Subjects & Themes.; Places.; Women Authors.; poetry.; Poetry.; Poésie.; Electronic books.